دور الحوسبة في إنجاز مشروع أنطولوجيا اللغة العربية التجارب - بوعامر, عمارية هديل (My University, 2024)
تقدم هذه الورقة البحثية نظرة عامة على دور الحوسبة في تطوير وإنجاز مشروع أنطولوجيا اللغة العربية، مع تقديم نظرة شاملة على التجارب والآفاق المستقبلية في هذا الميدان. بحيث يتناول البحث التطورات التقنية في مجال الحوسبة وتأثيرها على اللغة العربية من أجل إدخالها العالم الرقمي كونها من بين اللغات الأقل اهتماما في المجال التقني، مع التركيز على استخدام الحوسبة في تطوير وبناء المعاجم والموارد اللغوية التي من شأنها أن تسهم في بناء أنطولوجيا للغة العربية تثري المحتوى الرقمي العربي. كما يقدم البحث دراسة لتجارب سابقة في إنشاء أنطولوجيا للغة العربية باستخدام تقنيات الحوسبة، من بينها استخدام محرك البحث المعجمي، ولما تضمنه من تقنيات الحوسبة الفعالة في تنظيم البيانات اللغوية وتوفير واجهة مستخدم بسيطة سهلة الاستخدام للباحثين في مجال اللغويات. This research paper provides an overview of the role of computing in the development and completion of the Arabic language ontology project, while providing a comprehensive overview of experiences and future prospects in this field. The research addresses technical developments in the field of computing and their impact on the Arabic language in order to introduce it to the digital world as it is among the languages least interested in the technical field.With a focus on using computing to develop and build dictionaries and linguistic resources that would contribute to building an ontology for the Arabic language that enriches Arabic digital content. The research also presents a study of previous experiences in creating an ontology for the Arabic language using computing techniques, including the use of the lexical search engine, and because of the effective computing techniques it contains in organizing linguistic data and providinga simple, easy-to-use user interface for researchers in the field of linguistics
Keywords: الحوسبة ـ الأنطولوجيا ـ محرك البحث المعجمي ـ الموارد اللغويةـ المحتوى الرقمي; Computing – Ontology – Lexical search engine –linguisticResources - Digital content